The effects of nitrogen atmosphere pressure, constant and high-voltage pulse potentials of the substrate on the structure and properties of vacuum-arc ZrN coatings - Sobol’, O.V.; Andreev, A.A.; Stolbovoy, V.A.; Gorban’, V.F.; Pinchuk, N.V.; Meylekhov, A.A. (Вопросы атомной науки и техники, 2015)
ZrN-phase coatings with a cubic lattice (NaCl structure type) were produced by the method of vacuum-arc evaporation of a Zr cathode in nitrogen atmosphere at pressures PN between 0.02 and 0.64 Pa. The pressure increase at a bias potential of -150 V leads to formation of the growth texture [111] or to appearance of the bitextural state with the axes [111] and [311]. Additional pulsed-mode supply of high-voltage negative potential Uip = 800…2000 V, with pulse duration of 10 μs and frequency of 7 kHz, stimulates the emergence of texture [110]. At the substructure level, the Uip supply causes the microstrain relaxation and the crystallite size growth with increasing pressure. The observed changes are attributed to increased particle mobility and nitride formation activity under the action of Uip. The hardness increases with increasing pressure and reaches a value of 43 GPa. The Uip supply leads to a shift of the maximum hardness towards higher pressures.